Differentiation of Bone Marrow Mesenchymal Stem Cells to Cardiomyocyte-Like Cells Is Regulated by the Combined Low Dose Treatment of Transforming Growth Factor-β1 and 5-Azacytidine - Shutian Shi; Xingxin Wu; Xiao Wang; Wen Hao; Huangtai Miao; Lei Zhen; Shaoping Nie (Stem Cells International)
Bone marrow mesenchymal stem cells (BMMSCs) are used in cardiac tissue engineering for the regeneration of diseased hearts. We examined the differentiation of rat BMMSCs into cardiomyocyte-like cells when induced with a combined low dose treatment of transforming growth factor-β1 (TGF-β1) and 5-azacytidine (5-AZA). Results showed that cell proliferation in the combined low dose treatment group of TGF-β1 and 5-AZA was increased compared with the TGF-β1 group or the 5-AZA group. The cell apoptosis was relieved by combined TGF-β1 and 5-AZA treatment compared to 5-AZA treatment alone. The number of cells positive for myosin heavy chain, connexin-43, α-actin, and troponin I in the combined treatment group was higher than those observed in the TGF-β1 group or the 5-AZA group. Moreover, the combined low dose treatment group of TGF-β1 and 5-AZA reveals the strongest expression of troponin I, α-actin, and phosphorylated extracellular signal-regulated protein kinases 1 and 2 (p-ErK1/2) among the treatment groups. These results suggest that the combined low dose treatment of TGF-β1 and 5-AZA can improve the differentiation potential of rat BMMSCs into cardiomyocyte-like cells and alleviate cell damage effects in vitro. The mechanism that is involved in influencing differentiation may be associated with p-ErK1/2.